Determining the most suitable layout of space for the loading units’ handling in the maritime port - Stopka, Ondrej; Kampf, Rudolf (Transport, 2018)
The main advantages of maritime transport are (1) lowest costs, (2) large-scale carriage capacity, (3) carriage of different goods over long distances and (4) the most acceptable mode of transport in the context of the environment. This mode of transport is considered more profitable and more cost-effective than all other transport modes. Modern maritime ports have become the essential nodal components of freight transport networks. This paper is focused on determining the most suitable layout of space for the loading units warehousing and handling in the maritime port using the particular method. In the paper, four types of layout and five criteria were taken into account. Layout of warehousing and handling space can affect the entire transport process and can have a great effect on the economics of enterprises.First published online 11 April 2016